A literature review of energy waste in the manufacturing industry. (November 2022) - Geng, Duanyang; Evans, Steve
Highlights: We review 91 papers on energy waste by co-word based thematic analysis. We further review 500 papers on other energy topics by co-citation analysis. The characteristics of energy waste in the current literature are identified. The definition of energy waste is given based on the review results. A theoretical framework of energy waste is developed aligned with STS theory. Abstract: In order to respond to climate change, different governments set their own carbon neutrality targets by considering their own realities. Under such a circumstance, manufacturing companies are pressured to improve their energy performance so that their carbon emissions can be mitigated. Reducing energy waste from production systems is therefore critical. Many studies refer to energy waste, but few have illustrated the characteristics of energy waste, resulting in difficulty for those practitioners to continuously identify and eliminate such energy waste. This study conducts a literature review, covering publication from 1976 to February 2022, to propose narrow and broad definitions of energy waste to reduce or even eliminate energy waste, as well as a theoretical framework. A co-word-based thematic analysis and a co-citation analysis are conducted to understand the contents of energy waste and explore the links with existing energy-related concepts. The results reveal that many efforts have been made to reduce unnecessary energy consumption while there is no clear definition of energy waste, and the term "energy waste" has not been commonly recognized in the literature. Most of the previous studies proposed to reduce unnecessary energy consumption through management techniques, while in the meantime, digital technologies can facilitate such management. Both narrow and broad definitions of energy waste are proposed based on the findings, which contain management and technology perspectives. Design for energy waste elimination is further introduced. Aligning with the socio-technology system theory, we develop a theoretical framework that aims to comprehensively reduce energy waste. Future research directions include further understanding energy wastes by conducting case studies and developing a more detailed framework on energy waste.